Методика определения электромагнитных параметров и плотности тока в обмотках роторов асинхронных двигателей - Вербовой, А.П. (Електротехніка і електромеханіка, 2005)
Разработана методика определения электромагнитных параметров короткозамкнутой обмотки ротора асинхронного двигателя, которая отличается представлением короткозамкнутой обмотки ротора эквивалентной одновитковой обмоткой ( w₀₂ = 1, в литературе w₀₂ = 0,5 ) с числом фаз, равным числу фаз обмотки статора (m₀₂ = m₀₁, в литературе m₀₂ = Z₂ ). Новая методика позволяет рассчитывать значения электромагнитных параметров и плотность тока с более высокой точностью. Розроблена методика визначення електромагнітних параметрів при представленні короткозамкненої обмотки ротора асинхронного двигуна, яка відрізняється представленням короткозамкненої обмотки ротора еквівалентною одновитковою обмоткою ( w₀₂ = 1, в літературі w₀₂ = 0,5 ) з числом фаз, рівним числу фаз обмотки статора ( m₀₂ = m₀₁, в літературі m₀₂ = Z₂ ). Нова методика дозволяє розраховувати значення електромагнітних параметрів і щільність струму з вищою точністю. A technique for determination of electromagnetic parameters and current density in rotor windings of induction motors. This paper introduces a technique for determination of electromagnetic parameters of a squirrelcage rotor winding in an induction motor. The technique treats a squirrel cage rotor winding as an equivalent single-turn winding ( w₀₂ = 1, in publications on the subject w₀₂ = 0,5 ) with the number of phases equal to the number of the stator winding phases ( m₀₂ = m₀₁ , in publications m₀₂ = Z₂ ). The new technique makes it possible to calculate electromagnetic parameters and current density with higher accuracy.